Learning Methods and Critical Thinking Ability on Science Learning Outcomes - Jajang Bayu Kelana; Duhita Savira Wardani; Medita Ayu Wulandari (Jurnal Ilmiah Sekolah Dasar, 2021)
There are many ways that can be done in an effort to improve science learning outcomes in schools. One way is to choose the right learning method. This study aims to see the effect of experimental learning methods, expository learning methods and critical thinking skills on science learning outcomes. This research was conducted with a sample of 74 students. The research design used an experimental method with treatment by level 2 x 2. Data analysis used 2-way analysis of variance (ANOVA). The results of this study are that there are differences in the results of students learning science with experimental learning methods between students who learn using expository learning methods; there is an interaction between the learning method and students' critical thinking skills on science learning outcomes; The results of learning science between students who learn with experimental learning methods who have higher critical thinking skills are higher than students who learn using expository learning methods who have high critical thinking skills; The results of learning science between students who learn with experimental learning methods who have low critical thinking skills are lower than students who learn using expository learning methods who have low critical thinking skills. This study implies that the application of experimental learning methods can improve students' critical thinking skills so that it can improve student learning outcomes.